The Effect Of Giving Pure Honey Drink on The Reduction of Menstrual Pain (Dysmenorrhea) In Adolescent Private Vocational School - Winda Yunyaty Harianja; Anggita Septyani (LPPM AN NUUR, 2021)
Background: Menstrual pain is pain felt by women during menstruation until it can interfere with daily activities. Menstrual pain occurs in 60% -70% of women of productive age, 10 to 155 of whom are forced to lose their opportunities for work, school and family life. Honey is one of the non-pharmacological therapies that include herbal therapy, and has many nutrients since a long time ago, giving honey drinks is one of the herbal methods used to reduce menstrual pain. The purpose of this study was to determine the effect of drinking pure honey on reducing menstrual pain. Method: The type of research used was Pre Experiment with the One Group Pretest - Postest design, which was conducted at Muhammadiyah High School Purwodadu in June 2020 with a sample size of 12 class XI students. Results: The results showed that the provision of pure honey drink had an effect on reducing menstrual pain or dysminorrhea in XI grade students at Muhammadiyah High School Purwodadi as indicated by the value of P = 0.000 (P <0.05). Conclusion: There is a change in menstrual pain complaints before and after giving pure honey drink